(3GdChGFds - (3GdMSf Hf YHO Gddg Hf Sgd Hf SYjO GHf jMji Hf egQGf GdnYrSncQj, CHh gdGd,J (B395 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY QJHI Cgd GdCOH hPhjg s
(3BNQgG (B:s
(3bGd GHhgdGd GjOg Gddg hai gPG GdNHQ Odjd Ydi Cf GdCehGd GdPi YbOg fhad Hf YHO efGa Hjf GdYQH hGdaQS cGf s
(3Vefg ChGFd GdCTjGA ef GdCYeGd hGdCbhGd ai GdLGgdjg hGdESdGe heG fSH efgG Edi GdfHi Udi Gddg Ydjg hSde hEdi GdUMGHI hGdJGHYjf hGdedhc hGdQDSGA hGdbVGI hGdCHGAs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B240s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B126 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B2 s
Keywords: (3GdJGQjNs